Optimization of barracuda (Sphyraena spp.) utilization as a basis for strengthening fisheries logistics in Bangka Belitung, Indonesia - Siti Oftafia Wijayanti; Dareen Nadya Rema (Universitas Teuku Umar, 2025)
Central Bangka is a coastal area endowed with significant pelagic fishery resources. Barracuda fish (Sphyraena spp.) representing one of the economically valuable commodities, predominantly caught using handline fishing gear. However, the lack of adequate information on fishing seasons remains a major challenge in ensuring consistent supply, which in turn affects the efficiency of fisheries logistics and the stability of the distribution chain. This study aims to analyze the fishing seasonality, fishing effort, and distribution patterns of barracuda in Central Bangka as a basis for developing a more efficient and adaptive fisheries logistics system. The data used were obtained from monthly catch records and the number of handline fishing trips at the Batu Belubang Fish Landing Center (TPI) during the 2020–2024 period. The analysis involved calculating the Catch per Unit Effort (CPUE) and the Fishing Season Index (IMP) using the moving average method, followed by a comparative assessment between the IMP values and fishing effort patterns to evaluate fishermen’s responsiveness to seasonal fish availability. The results indicated that peak fishing seasons for barracuda occur in January, March, May–June, and October. Nevertheless, a mismatch between fishing effort and IMP values was observed, indicating both overcapacity and undercapacity during certain periods. These inefficiencies contribute to imbalances in the supply and distribution of barracuda. Among the identified peak months, May was determined to be the most efficient period for barracuda fishing in Central Bangka waters